Sustainability of social enterprises in the post-pandemic world: Business lessons learned - Stefan Chichevaliev (University American College Skopje, 2021)
Social entrepreneurship gradually becomes a priority choice for international organizations, financial partners and other players on the market in terms of investment and doing business while achieving a social purpose. Covid-19 has increased the recognition of social entrepreneurs as advocates for change which contribute to the mitigation of the impact of the pandemic and the increased efforts to build back better towards a resilient recovery. However, social enterprises need a conducive business environment to thrive and fulfil their potential. The business dimension is one of the key factors for development of social entrepreneurship. The business environment in which social enterprises operate is a transversal topic in terms of policy, stakeholders and social outcomes. Conducive business environment fosters early entrepreneurial activity and access and engagement of social entrepreneurs on the market which present the prerequisite for development of the sector. This paper presents the results related to the business dimension from broader holistic research of the macro-environment conducted in the period October - December 2019 and a follow up a year later. Qualitative methodology was used, through conducting interviews with social entrepreneurs and key stakeholders, combined with document analysis to provide an insight into the business challenges and needs of social enterprises in North Macedonia. The evidence showed that access to market and funding, room for innovation, collaboration with the business sector and lack of public and customer recognition are some of the crucial issues for the development of social entrepreneurship in the country. The country's current business scenery is not enabling for traditional businesses which makes it even more perplexing for social enterprises. Social enterprises need conducive policies that facilitate business operations, but also empower intersectoral partnerships and collaboration.
Keywords: 330; social entrepreneurship; ecosystem; business; key factors; post pandemic; sus- tainability; policies; social entrepreneurs